Cystitis glandularis due to Escherichia coli infection in a diabetic Miniature Schnauzer: a case report - J. P. Rey Amunategui; D. Echeverria; A. Duchene (BMC Veterinary Research)
Abstract Background Lower urinary tract disease is a common clinical condition in dogs, usually presenting with dysuria, pollakiuria and haematuria. Diabetes mellitus is a predisposing factor for urinary tract infection in both humans and dogs and does not necessarily present with clinical signs. In this case report, we describe for the first time a case of cystitis glandularis in a dog with diabetes mellitus, associated with Escherichia coli urinary tract infection. Case presentation A 12 year old 9.2-kg (20.2-lb) castrated male Miniature Schnauzer with diabetes mellitus, was referred because of continued dysuria, pollakiuria and hematuria without a satisfactory response to treatment. The abdominal ultrasound revealed an irregular increase in mural thickness of the bladder, together with multiple immobile structures, apparently originating on the dorsal surface, of varied longitudinal diameters, with a convex hyperechogenic interface with an acoustic shadow. It was decided to perform a surgical cystotomy, which revealed that the surface of the urothelium showed dark hemorrhagic staining and multiple nodular structures, which were relatively hard to palpate. Histological examination of the bladder wall revealed hyperplastic urothelial epithelium, submucosal glandular formations with well differentiated mature cells and a chorion with signs of edema, concluding a diagnosis of cystitis glandularis. Bacteriological culture of the urothelium and urine revealed Escherichia coli infection. After initiation of antibiotic therapy and pain management, the dog's clinical signs improved markedly until complete remission of the bladder lesions. Conclusion Although there have been few reports of this clinical presentation in veterinary medicine, two in cats and one in a female schnauzer, this is the first reported case of cystitis glandularis associated with urinary tract infection due to Escherichia coli. The importance of bacteriological and histopathological studies in the diagnosis of urinary tract pathologies should be emphasized.